The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s10554-020-02126-7
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial strain rate during atrial contraction predicts raised pulmonary capillary wedge pressure: evidence for left atrio-ventricular interaction

Abstract: This study aimed to assess the relationship between different LA strain components and PCWP as well as to the relationship with other established methods. We studied 144 symptomatic patients, age 63 ± 14 years, 54 males, using conventional transthoracic echocardiography protocols, including LA and LV myocardial deformation from speckle tracking technique investigations along with simultaneous right heart catheterization (RHC) using established techniques. From RHC, pulmonary artery pressure (PAP), and pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Our study also confirms significant impairment of the reservoir function, with similar conduit function in HFpEF compared to preHF group. Of note all LA strain and strain rate parameters had very good reproducibility in our study, similar to the most recent publications [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study also confirms significant impairment of the reservoir function, with similar conduit function in HFpEF compared to preHF group. Of note all LA strain and strain rate parameters had very good reproducibility in our study, similar to the most recent publications [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Lindqvist et al [ 34 ], in a recent publication, demonstrated using invasive evaluation of the LA pressure, that SR_CT was the best accurate component of LA deformation measurements that correlated with PCWP. This parameter had superior accuracy in predicting elevated PCWP compared to recently proposed uni- and multivariable-based algorithms (r 2 = 0.60, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Left atrial strain (LAS) analysis by speckle tracking echocardiography (STE) is a relatively new method for evaluating LA function [4][5][6]. Some reports have highlighted the role of LAS in predicting the recurrence of AF after ablation [7] and a relationship between LAS values and invasively estimated left atrial pressure (LAP) values [8,9]. High LAP has proven to be an independent predictor of symptomatic AF recurrence after catheter ablation and has been associated with advanced LA remodeling [10].…”
Section: Introductionmentioning
confidence: 99%
“…The load alteration during CPAP interventions has been shown to be associated with a small change in LV GLS with simultaneous change in LAS during the same cardiac cycle [ 14 ]. Our findings confirm this interaction (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%